EFFICACY OF POST-EMERGENCE HERBICIDES ON WEED CONTROL, PRODUCTIVITY AND ECONOMICS OF SUGARCANE - U , VIJAYA BHASKAR REDDY (The Journal of Research ANGRAU, 2026)
A field experiment in sugarcane weed control was conducted from 2020-21 to 2022-23 inrandomized block design with three replications in alluvial soils of Krishna – Godavari delta ofAndhra Pradesh. Results revealed that, comparatively higher weed control efficiency was recordedwith post-emergence application of tembotrione @ 125 g/ha + halosulfuran methyl @ 125 g/ha fbIC at 60 and 90 DAP. Significantly more cane yield was recorded with application of topramezone@ 40 g/ha + halosulfuron methyl @ 125 g/ha fb IC at 60 and 90 DAP (115.9 t/ha) which washowever statistically at par with rest of the herbicide treatments. The quality parameters likesucrose %, CCS and purity % were not affected by the herbicide treatments. With regard toeconomics, higher gross returns (Rs. 3,43,296), net returns (Rs. 45,130/-) and B:C ratio (1.15)was recorded with topramezone @ 40 g/ha + halosulfuron methyl @ 125 g/ha fb IC at 60 and 90DAP